2016
DOI: 10.31849/forestra.v11i2.152
|View full text |Cite
|
Sign up to set email alerts
|

KAJIAN EKOLOGI PASAK BUMI (Eurycoma longifolia Jack) DAN PEMANFAATAN OLEH MASYARAKAT DI SEKITAR HUTAN LARANGAN ADAT RUMBIO, KABUPATEN KAMPAR PROVINSI RIAU

Abstract: Pasak bumi is one kind of medicinal plants commonly consumed by people and grow in Prohibition of Indigenous Forests Rumbio. Information on the ecological conditions Pasak bumi in Prohibition of Indigenous Forests Rumbio is important known as an indicator of the presence of Pasak bumi, and their population in the forest. The purpose of this study to analyze the ecological conditions Pasak bumi in Prohibition of Indigenous Forests Rumbio , and know how to use Pasak bumu conducted by people around the Prohibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
1
2
0
9
Order By: Relevance
“…The IVI of E. longifolia at seedling and sapling stages decreased significantly from the highest to the 8 th . Similar result was also obtained by Kartikawati et al (2014) in Kubu Raya district and Hasibuan et al (2016) in Rumbio Forest who found that at the seedling stage E. longifolia was abundant but decreased significantly in sapling and mature stages. However, in certain sites, there is an exception that E. longifolia may grow to a "giant" size, where the species may reach more than 20 cm in diameter and more than 7 m in height.…”
Section: Species Compositionsupporting
confidence: 86%
See 1 more Smart Citation
“…The IVI of E. longifolia at seedling and sapling stages decreased significantly from the highest to the 8 th . Similar result was also obtained by Kartikawati et al (2014) in Kubu Raya district and Hasibuan et al (2016) in Rumbio Forest who found that at the seedling stage E. longifolia was abundant but decreased significantly in sapling and mature stages. However, in certain sites, there is an exception that E. longifolia may grow to a "giant" size, where the species may reach more than 20 cm in diameter and more than 7 m in height.…”
Section: Species Compositionsupporting
confidence: 86%
“…Based on the interviews with local people, in Tor siparapara forest, pasak bumi roots were commonly harvested at sapling and pole stages. The same case also occurred in Rumbio forest, Riau according to Hasibuan et al (2016). According to Zulfahmi et al (2015), another factor that explains the low number of sapling and pole stages is the high demand for this product.…”
Section: Species Compositionmentioning
confidence: 72%
“…Tumbuhan ini banyak ditemukan di hutan Indonesia, Malaysia, Thailand, Filipina, Vietnam, dan Myanmar (Andasari dan Navia, 2019). Spesies ini memiliki banyak manfaat sebagai obat bagi kesehatan manusia, terutama dikenal untuk aprodisiak (Soedjito, 1988;Hasibuan et al, 2016). Ekstrak akar pasak bumi mengandung beberapa senyawa berkhasiat obat, seperti senyawa eurycomanone, eurycomanol, eurycomalactone, canthine-6-one alkaloid, 9-hydroxycanthin-6-one, 14,15β-dihydroxyklaineanone, komponen fenol, tanin, quanissoid, dan triterpenoid (Tada et al, 1991;Kuo et al, 2003;Nurhanan et al, 2005;Arbain et al, 2014;Hajjouli et al, 2014;Tran et al, 2014).…”
Section: Pendahuluanunclassified
“…Senyawasenyawa tersebut dapat dimanfaatkan sebagai obat antimalaria, mencegah kanker payudara, bahan insektisida meningkatkan hormon testosterone, dan mencegah osteoporosis (Effendy et al, 2012). Pemanfaatan pasak bumi sebagai obat telah dilakukan oleh masyarakat lokal di Riau, Lampung dan Belitungsecara turuntemurun (Heyne, 1987;Hasibuan et al, 2016).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation